Current collector and its manufacturing method and use

The current collector design, featuring a fiber base layer and adhesive metal layers, addresses the challenges of weight and energy density in lithium-ion batteries by enhancing bonding and preventing metal layer detachment, resulting in a lighter, more efficient battery.

JP2025514399APending Publication Date: 2025-05-02YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024563915
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-05-27
Filing Date
2023-05-04
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Current lithium-ion battery current collectors are heavy, contributing to low energy density and high manufacturing costs, with conventional foil manufacturing limitations preventing further thickness reduction without compromising strength and processing performance.

Method used

A current collector comprising a fiber base layer with composite fibers, inorganic fillers, and an auxiliary agent, sandwiched between adhesive layers and metal layers, which enhances bonding and prevents metal layer detachment, allowing for reduced thickness and weight while maintaining strength.

Benefits of technology

The proposed current collector design reduces battery weight, improves energy density, prevents metal layer detachment, and lowers manufacturing costs by enabling thinner, stronger current collector structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025514399000001_ABST
    Figure 2025514399000001_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of batteries, and in particular to current collectors and their manufacturing methods and uses. [Solution] The current collector includes a fiber base layer, a first adhesive layer and a second adhesive layer are provided on both surfaces of the fiber base layer, and a first metal layer and a second metal layer are provided on the surfaces of the first adhesive layer and the second adhesive layer that are away from the fiber base layer, respectively, and the material of the fiber base layer includes, by weight, 50 to 120 parts of composite fiber, 4.1 to 19 parts of inorganic filler, and an auxiliary, where the composite fiber includes organic fiber and inorganic fiber. The current collector according to the present invention can reduce the weight of the battery and prevent the metal layer from falling off.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of batteries, and in particular to current collectors and their manufacturing methods and uses. [Background technology]

[0002] At present, the positive and negative current collectors of lithium-ion batteries are basically made of pure copper foil as the negative current collector and pure aluminum foil as the positive current collector, so the total mass of the positive and negative current collectors is heavy and accounts for 15% to 20% of the total battery mass. By making the positive and negative current collectors thinner, the weight of the battery can be reduced and the energy density can be improved. However, at present, pure aluminum foil is generally produced by conventional rolling equipment, and the thinnest thickness of mass production is about 8 μm. Pure copper foil is generally an electrolytic copper material, which is precipitated and pressed by a cathode roller, and the thinnest thickness of mass production is about 6 μm. Due to the limitations of current technical equipment, it is difficult to further reduce the thickness of copper foil or aluminum foil, and after copper and aluminum become foil materials, their own strength decreases, which reduces their processing performance, making it difficult to further thin them.

[0003] Currently, there are studies on reducing the weight of batteries, improving the energy density, reducing costs, and realizing lightweight batteries by depositing aluminum or copper on plastic thin films (e.g., PET films, PVT films, PP films, etc.) using physical or chemical vapor deposition technology to form current collectors. However, the plastic thin films used are highly ductile and therefore easily deformed. Furthermore, in order to better match the conductivity of conventional foil materials, it is usually necessary to increase the deposition thickness of the copper or aluminum layer to about 2 μm, and the copper or aluminum layer is prone to falling off due to the increased thickness. Summary of the Invention [Problem to be solved by the invention]

[0004] As a result, the present invention provides a current collector that can reduce the weight of a battery and prevent the metal layer from falling off, as well as a manufacturing method and use thereof. [Means for solving the problem]

[0005] In order to achieve the above object of the present invention, the following technical proposals have been made.

[0006] In one aspect of the present invention, there is provided a current collector including a fiber base layer, A first adhesive layer and a second adhesive layer are provided on both surfaces of the fiber base layer, and the first adhesive layer and the second adhesive layer are provided with a first metal layer and a second metal layer on the surfaces away from the fiber base layer, respectively; A current collector is provided, the material composition of the fiber-based layer comprising, by weight, 50-120 parts of composite fiber, 4.1-19 parts of inorganic filler, and an auxiliary, with the proviso that the composite fiber comprises organic fiber and inorganic fiber.

[0007] Preferably, in the current collector described above, the mass ratio of the organic fibers to the inorganic fibers is (70-99.9):(0.1-30).

[0008] Preferably, in the current collector described above, the mass ratio of the organic fibers to the inorganic fibers is (90-99.9):(0.1-10).

[0009] Preferably, in the current collector described above, the inorganic filler includes one or more of calcium carbonate, borax, and nanosilica.

[0010] Preferably, in the current collector described above, the organic fibers include one or more of polyethylene terephthalate fibers, polybutylene terephthalate fibers, polyethylene naphthalate fibers, polypropyl urethane fibers, polyurethane fibers, polycaprolactone fibers, nylon 6, nylon 66, polyimide fibers, polyacrylonitrile fibers, polyethylene oxide fibers, polyvinyl alcohol fibers, polyvinyl chloride fibers, polyvinylpyrrolidone fibers, cellulose acetate, ethylcyanate ethyl cellulose, polyaniline fibers and polybenzimidazole fibers.

[0011] Preferably, in the current collector described above, the inorganic fibers include one or more of graphene fibers, carbon fibers, glass fibers, ceramic fibers, metal oxide nanofibers, and silica nanofibers.

[0012] Preferably, in the current collector described above, the auxiliary includes one or more of a dispersant, a thickener, an emulsifier, and a binder, The dispersing agent comprises one or more of polyacrylamide, polyvinyl alcohol, sodium citrate, and sodium silicate; The viscosity increasing agent may comprise one or more of sodium hydroxypropyl methylcellulose, sodium hydroxyethyl methylcellulose, sodium carboxymethylcellulose, sodium methylcellulose and sodium alginate; The emulsifier comprises one or more of glyceryl monostearate, polyoxyethylene ether, and sodium dodecyl sulfate; The binder includes sodium carboxymethylcellulose and / or polyvinyl alcohol.

[0013] Preferably, in the above-mentioned current collector, the amount of the auxiliary agent added to the fiber base layer is 8.1 to 28 parts by weight, and the auxiliary agent contains 2.5 to 9 parts by weight of the dispersant, 3 to 8 parts by weight of the thickener, 0.1 to 2 parts by weight of the emulsifier, and 2.5 to 9 parts by weight of the binder.

[0014] Preferably, the above-mentioned current collector further includes a first oxidation-resistant layer and a second oxidation-resistant layer, the first oxidation-resistant layer being located on a surface of the first metal layer remote from the first adhesive layer, and the second oxidation-resistant layer being located on a surface of the second metal layer remote from the second adhesive layer.

[0015] Preferably, in the current collector described above, the materials of the first adhesive layer and the second adhesive layer are each independently Ni, Zn, Fe, Gr, SiO2, Al2O3, Fe2O3 or Si3N4.

[0016] Preferably, in the current collector described above, the material of the first metal layer and the second metal layer is Al, Cu or Zn.

[0017] Preferably, in the current collector described above, the materials of the first oxidation-resistant layer and the second oxidation-resistant layer are each independently Al, Fe, Ni, Zn, Gr, Fe2O3, Al2O3, SiC or Si3N4.

[0018] Preferably, in the current collector described above, the fiber base layer has a thickness of 2 μm to 8 μm.

[0019] Preferably, in the current collector described above, the first adhesive layer and the second adhesive layer each independently have a thickness of 10 nm to 200 nm.

[0020] Preferably, in the current collector described above, the first metal layer and the second metal layer each independently have a thickness of 100 nm to 2000 nm.

[0021] Preferably, in the current collector described above, the first oxidation-resistant layer and the second oxidation-resistant layer each independently have a thickness of 10 nm to 100 nm.

[0022] Preferably, in the current collector described above, the material of at least one of the first adhesive layer and the second adhesive layer is Fe, and the inorganic fibers include one or both of graphene fibers and carbon fibers.

[0023] Preferably, in the current collector described above, the inorganic fibers are selected from metal oxide nanofibers, and the materials of the first adhesive layer and the second adhesive layer are each independently selected from metals or metal oxides.

[0024] Preferably, in the above-mentioned current collector, the inorganic fibers are one or more types selected from graphene fibers, carbon fibers, glass fibers, ceramic fibers, and silica nanofibers, and the materials of the first adhesive layer and the second adhesive layer are each independently selected from non-metal oxides and non-metal nitrides.

[0025] As one aspect of the present invention, there is provided a method for producing the current collector described above, comprising the steps of: mixing the composite fiber, the inorganic filler and the auxiliary, and then rolling the resulting mixture to produce the fiber base layer; forming the first adhesive layer and the second adhesive layer on both sides of the fiber-based layer, respectively; and There is further provided a method of manufacturing a current collector, comprising forming the first metal layer and the second metal layer on one side of the first adhesive layer and the second adhesive layer, respectively, facing away from the fiber-based layer.

[0026] In another aspect of the present invention, there is further provided an electrode strip comprising the current collector described above and an electrode active material layer disposed on a surface of the current collector.

[0027] In another aspect of the present invention, there is provided a cell including the above-described electrode piece.

[0028] According to one aspect of the present invention, there is further provided a battery pack including a plurality of the above-described electrode units.

[0029] As another aspect of the present invention, there is further provided a power consuming device comprising a cell as described above or a battery pack as described above. Effect of the Invention

[0030] The fiber base layer according to the present invention has low elongation and is not easily deformed, and does not require perforation treatment on the surface of the fiber base layer. Under the action of the first adhesive layer and the second adhesive layer, good bonding with the first metal layer and the second metal layer can be achieved, and the first metal layer and the second metal layer are prevented from falling off, and the problem of weakening or loss of battery performance due to the falling off of the first metal layer and the second metal layer is solved. In addition, the fiber base layer can further reduce the weight of the current collector, reduce the total weight of the battery, and improve its energy density. The introduction of the fiber base layer is favorable for the infiltration of the current collector and the electrolyte, which improves the efficiency of the liquid injection process of the battery, improves the multiplication performance of the battery, and reinforces the stability of the battery.

[0031] In summary, the current collector according to the present invention realizes a reduction in the weight of the battery, improves the energy density of the battery, prevents the metal plating layer from falling off, and reduces the manufacturing costs of the current collector and the battery. [Brief description of the drawings]

[0032] In order to more clearly describe the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly describes the drawings that need to be used in the description of the specific embodiments or the prior art. Obviously, the drawings in the following description are only some examples of the present invention, and those skilled in the art can obtain other drawings based on these drawings without paying creative labor.

[0033] [Figure 1] FIG. 2 is a structural schematic diagram of a current collector manufactured in an embodiment of the present invention. [Explanation of symbols]

[0034] 100: fiber base layer; 200: first adhesive layer; 300: first metal layer; 400: first oxidation resistant layer; 500: second adhesive layer; 600: second metal layer; 700: second oxidation resistant layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] Reference is now made in detail to embodiments of the present invention, one or more examples of which are described below. The provision of each example is for interpretation only and is not intended to limit the present invention. Indeed, it will be apparent to those skilled in the art that multiple modifications and variations can be made to the present invention without departing from the scope or spirit of the invention. For example, features illustrated or described as part of one embodiment can be used with other embodiments to produce still further embodiments.

[0036] Therefore, it is intended that the present invention cover such modifications and variations as fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present invention are disclosed in or become apparent from the following detailed description. Those skilled in the art should appreciate that this discussion is merely intended to illustrate exemplary embodiments and is not intended to limit the broader aspects of the present invention.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. In this specification, the terms used in the description of the present embodiment are merely for describing specific embodiments and are not intended to limit the present invention. As used herein, the term "and / or" includes any and all combinations of one or more associated listed items.

[0038] Conventional current collectors are heavy, which results in a heavy total battery weight and low energy density. In addition, the plastic thin film currently used to reduce the weight of the current collector has a high degree of elongation and is easily deformed, and the metal layer deposited thereon is easily removed, making it difficult to substantially improve the performance of the battery. Therefore, the present invention provides a current collector to solve the above problems.

[0039] The current collector according to the present invention comprises a fiber base layer, and a first adhesive layer and a second adhesive layer are provided on both surfaces of the fiber base layer, respectively, and a first metal layer and a second metal layer are provided on the surfaces of the first adhesive layer and the second adhesive layer that are away from the fiber base layer, respectively; The material of the fiber-based layer comprises, by weight, 50-120 parts of composite fiber, 4.1-19 parts of inorganic filler and auxiliary agents, where the composite fiber comprises organic fiber and inorganic fiber.

[0040] The fiber-based layer has low elongation and is not easily deformed, and does not require perforation treatment on the surface of the fiber-based layer. Under the action of the first adhesive layer and the second adhesive layer, good bonding with the first metal layer and the second metal layer can be achieved, and the first metal layer and the second metal layer are prevented from falling off, and the problem of weakening or loss of battery performance due to the falling off of the first metal layer and the second metal layer is solved. In addition, the fiber-based layer can further reduce the weight of the current collector, reduce the total weight of the battery, and improve its energy density. The introduction of the fiber-based layer is favorable for the infiltration of the current collector and the electrolyte, which improves the efficiency of the liquid injection process of the battery, improves the magnification performance of the battery, and reinforces the stability of the battery.

[0041] In summary, the current collector according to the present invention realizes a reduction in the weight of the battery, improves the energy density of the battery, prevents the metal plating layer from falling off, and reduces the manufacturing costs of the current collector and the battery.

[0042] In some embodiments, the bicomponent fiber may be any value between 50 and 120 parts, such as 55 parts, 58 parts, 60 parts, 65 parts, 70 parts, 80 parts, 90 parts, 100 parts, 110 parts.

[0043] In some embodiments, the mass ratio of organic fibers to inorganic fibers may be any value between (70-99.9):(0.1-30), and may be 80:20, 82:18, 85:15, 87:13, 90:10, 92:8, 95:5, or 98:2.

[0044] In some embodiments, the organic fiber may be any organic fiber commonly used in the art, including, but not limited to, one or more of polyethylene terephthalate fiber, polybutylene terephthalate fiber, polyethylene naphthalate fiber, polypropyl urethane fiber, polyurethane fiber, polycaprolactone fiber, nylon 6, nylon 66, polyimide fiber, polyacrylonitrile fiber, polyethylene oxide fiber, polyvinyl alcohol fiber, polyvinyl chloride fiber, polyvinylpyrrolidone fiber, cellulose acetate, ethylcyanoethyl cellulose, polyaniline fiber, and polybenzimidazole fiber. Preferably, the organic fiber is one or more of nylon 6, nylon 66, polyimide fiber, and polyacrylonitrile fiber.

[0045] In some embodiments, the inorganic fiber may be any inorganic fiber known in the art, including but not limited to one or more of graphene fiber, carbon fiber, glass fiber, ceramic fiber, metal oxide nanofiber, and silica nanofiber. Preferably, the inorganic fiber is a metal oxide nanofiber. Wherein, the metal oxide nanofiber includes one or more of aluminum oxide nanofiber, zinc oxide nanofiber, zirconium oxide nanofiber, magnesium oxide nanofiber, titanium dioxide nanofiber, and tin oxide nanofiber. Wherein, the graphene fiber is a fibrous material composed of graphene monolayer units.

[0046] In some embodiments, the inorganic filler comprises one or more of calcium carbonate, borax and nanosilica.The addition of inorganic filler can improve the mechanical and heat resistance performance of the fiber-based layer.Preferably, the inorganic filler is calcium carbonate, borax and nanosilica.

[0047] In some embodiments, the inorganic filler is 2-8 parts by weight of calcium carbonate, 2-10 parts by weight of borax, and 0.1-1 parts by weight of nanosilica.

[0048] In some embodiments, the auxiliary may include one or more of a dispersant, a thickener, an emulsifier, and a binder, wherein the dispersant may be one or more of polyacrylamide, polyvinyl alcohol, sodium citrate, and sodium silicate, the thickener may be one or more of hydroxypropylmethylcellulose sodium, hydroxyethylmethylcellulose sodium, carboxymethylcellulose sodium, methylcellulose sodium, and sodium alginate, the emulsifier may be one or more of glyceryl monostearate, polyoxyethylene ether, and sodium dodecyl sulfate, and the binder may be sodium carboxymethylcellulose and / or polyvinyl alcohol.

[0049] In some embodiments, the amount of the auxiliary agent added to the fiber base layer may be 8.1 to 28 parts by weight, and the auxiliary agent may be 2.5 to 9 parts by weight of a dispersant, 3 to 8 parts by weight of a thickener, 0.1 to 2 parts by weight of an emulsifier, and 2.5 to 9 parts by weight of a binder.

[0050] In some embodiments, the fiber-based layer may have a thickness of any value between 2 μm and 8 μm, such as 2.5 μm, 4 μm, 5.5 μm, 6 μm, 7 μm.

[0051] In some embodiments, the fiber-based layer has a tensile elongation of 0.2% to 0.4% at a press density of 4 g / cm3 to 4.1 g / cm3, which is significantly lower than the elongation of conventional copper foils or aluminum foils (over 0.6%), and the current collector thus manufactured has lower elongation and is less prone to deformation.

[0052] In some embodiments, the surface of the fibrous base layer may or may not have a pore structure, and if it does, the average pore size may be between 5 nm and 500 nm, and the porosity may be between 0.1% and 50%.

[0053] In some embodiments, the thickness of the first adhesive layer and the second adhesive layer may each independently be any value between 10 nm and 200 nm, for example, 30 nm, 50 nm, 100 nm, 130 nm, 150 nm, 180 nm.

[0054] In some embodiments, the materials of the first adhesive layer and the second adhesive layer are independently selected from metals or nonmetallic compounds. The metals may be Ni, Zn, Fe, or Gr, and the nonmetallic compounds are mainly oxides and nitrides, such as SiO2, Al2O3, Fe2O3, or Si3N4. The nonmetallic compounds are further divided into compounds containing metal elements and compounds not containing metal elements. The compounds containing metal elements mainly include metal oxides, such as Al2O3 or Fe2O3, and the compounds not containing metal elements mainly include nonmetallic oxides and nonmetallic nitrides, such as SiO2 or Si3N4.

[0055] In some embodiments, the inorganic fibers are selected from metal oxide nanofibers and the materials of the first and second adhesive layers are each independently selected from metals or metal oxides.

[0056] In some embodiments, the inorganic fibers comprise titanium dioxide nanofibers and the materials of the first and second adhesive layers are each independently selected from Ni and Fe2O3.

[0057] In some embodiments, the inorganic fibers are one or more selected from graphene fibers, carbon fibers, glass fibers, ceramic fibers, and silica nanofibers, and the materials of the first and second adhesive layers are each independently selected from non-metal oxides and non-metal nitrides, such as SiO2 or Si3N4.

[0058] In some embodiments, the inorganic fibers are one or more selected from glass fibers, ceramic fibers, and silica nanofibers, and the materials of the first and second adhesive layers are each independently selected from SiO 2 or Si 3 N 4 .

[0059] In some embodiments, the inorganic fibers are one or two selected from graphene fibers and carbon fibers, and the materials of the first adhesive layer and the second adhesive layer are each independently selected from Ni, Zn, Fe, and Gr.

[0060] In some embodiments, the inorganic fibers are one or two selected from graphene fibers and carbon fibers, and at least one material of the first adhesive layer and the second adhesive layer is Fe.

[0061] In some embodiments, the thickness of the first metal layer and the second metal layer may each independently be any value between 100 nm and 2000 nm, for example, 150 nm, 200 nm, 300 nm, 500 nm, 800 nm, 1200 nm, 1500 nm, 1800 nm.

[0062] In some embodiments, the material of the first metal layer and the second metal layer may be Al, Cu or Zn.

[0063] In some embodiments, the current collector further includes a first oxidation-resistant layer and a second oxidation-resistant layer, the first oxidation-resistant layer being located on one side of the first metal layer away from the first adhesive layer, and the second oxidation-resistant layer being located on one side of the second metal layer away from the second adhesive layer. The introduction of the oxidation-resistant layer can prevent the first metal layer and the second metal layer from being oxidized, and can further prevent the first metal layer and the second metal layer from falling off.

[0064] In some embodiments, the thickness of the first oxidation-resistant layer and the second oxidation-resistant layer may each independently be any value between 10 nm and 100 nm, for example, 20 nm, 50 nm, 70 nm, or 90 nm.

[0065] In some embodiments, the materials of the first and second oxidation-resistant layers may be independently a metal, a metal oxide, or a non-metallic compound, where the metal may be Al, Fe, Ni, Zn, or Gr, the metal oxide may be Fe2O3 or Al2O3, and the non-metallic compound may be a carbide or nitride, such as SiC or Si3N4. Preferably, when the material of the first and second metal layers is Cu, the materials of the first and second oxidation-resistant layers may be independently Al, Fe, Ni, Zn, Fe2O3, Al2O3, or SiC, and when the material of the first and second metal layers is Al, the materials of the first and second oxidation-resistant layers may be independently Ni, Gr, Al2O3, or Si3N4.

[0066] As one aspect of the present invention, there is provided a method for producing the current collector described above, comprising the steps of: Mixing the composite fiber, the inorganic filler and the auxiliary agent, and then rolling the mixture to prepare a fiber-based layer; forming a first adhesive layer and a second adhesive layer on both sides of the fiber-based layer, respectively; forming a first metal layer and a second metal layer on a side of the first adhesive layer and a side of the second adhesive layer away from the fiber-based layer, respectively.

[0067] In some embodiments, the specific steps of preparing the fiber-based layer may include mixing composite fibers, inorganic fillers and auxiliary agents, laying them in a net shape, and then shaping them by hot rolling and drying.

[0068] In some embodiments, the method of forming the first adhesion layer, the second adhesion layer, the first metal layer, and the second metal layer may be any method known in the art, such as vacuum deposition.

[0069] In another aspect of the present invention, there is further provided an electrode strip comprising the current collector described above and an electrode active material layer disposed on a surface of the current collector.

[0070] In another aspect of the present invention, there is provided a cell including the above-described electrode piece.

[0071] According to one aspect of the present invention, there is further provided a battery pack including a plurality of the above-described electrode units.

[0072] As another aspect of the present invention, there is further provided a power consuming device comprising a cell as described above or a battery pack as described above.

[0073] The present invention will be described in detail below with reference to specific examples and comparative examples.

[0074] Example 1 The structural schematic diagram of the current collector manufactured in this embodiment is shown in Figure 1. As can be seen from Figure 1, the current collector includes a fiber-based layer 100, in which a first adhesive layer 200 and a second adhesive layer 500 are respectively provided on both sides of the fiber-based layer 100. The first adhesive layer 200 and the second adhesive layer 500 are respectively provided with a first metal layer 300 and a second metal layer 600 on one side away from the fiber-based layer 100. The first metal layer 300 and the second metal layer 600 are respectively provided with a first oxidation-resistant layer 400 and a second oxidation-resistant layer 700 on one side away from the first adhesive layer 200 and the second adhesive layer 500. Specifically, the manufacturing steps of the current collector are as follows:

[0075] 1) Manufacturing the fiber base layer 100 Nylon 6 and titanium dioxide nanofibers were mixed and melted in a mass ratio of 98:2, and then extruded to form a composite fiber. 50 parts of the composite fiber, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica were mixed uniformly, and then laid uniformly in a net shape, followed by hot rolling and drying to produce a fiber base layer 100 with a thickness of 6 μm.

[0076] 2) Manufacturing of current collectors By using vacuum deposition technology, the first adhesive layer 200 and the second adhesive layer 500 with a thickness of 50 nm were respectively deposited on the upper and lower surfaces of the fiber-based layer 100 produced in step 1), where the first adhesive layer 200 and the second adhesive layer 500 are nickel metal layers. Then, the first metal layer 300 and the second metal layer 600 with a thickness of 1000 nm were subsequently deposited on the first adhesive layer 200 and the second adhesive layer 500, where the first metal layer 300 and the second metal layer 600 are aluminum metal layers. Then, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 with a thickness of 50 nm were subsequently deposited on the first metal layer 300 and the second metal layer 600, where the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 are nickel metal layers, that is, an aluminum current collector was obtained. The relevant performance test was carried out thereon, and the test results are shown in Table 1.

[0077] Example 2 The current collector manufacturing method and structure of this embodiment are basically the same as those of the current collector of the embodiment 1, except that the first metal layer 300 and the second metal layer 600 in step 2) are copper metal layers to manufacture a copper current collector. The relevant performance tests were carried out on the copper current collector, and the test results are shown in Table 1.

[0078] Example 3 The manufacturing method and structure of the current collector in this embodiment are basically the same as those in Example 1, but the difference is in the composition of the fiber base layer 100. Specifically, the manufacturing steps of the current collector are as follows.

[0079] 1) Manufacturing the fiber base layer 100 Nylon 6 and titanium dioxide nanofibers were mixed and melted in a mass ratio of 98:2, and then extruded to form a composite fiber. 80 parts of the composite fiber, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica were mixed uniformly, and then uniformly laid in a net shape, followed by hot rolling and drying to produce a fiber base layer 100 with a thickness of 6 μm.

[0080] 2) Manufacturing of current collectors By using vacuum deposition technology, a first adhesive layer 200 and a second adhesive layer 500 with a thickness of 50 nm were respectively deposited on the upper and lower surfaces of the fiber-based layer 100 produced in step 1). However, the first adhesive layer 200 and the second adhesive layer 500 are SiO2 layers. Then, a first metal layer 300 and a second metal layer 600 with a thickness of 1000 nm were subsequently deposited on the first adhesive layer 200 and the second adhesive layer 500. However, the first metal layer 300 and the second metal layer 600 are aluminum metal layers. Then, a first oxidation-resistant layer 400 and a second oxidation-resistant layer 700 with a thickness of 50 nm were subsequently deposited on the first metal layer 300 and the second metal layer 600. However, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 are Al2O3 layers, that is, an aluminum current collector was obtained. The relevant performance test was carried out thereon, and the test results are shown in Table 1.

[0081] Example 4 The current collector manufacturing method and structure of this embodiment are basically the same as those of the current collector of the embodiment 3, but the difference is that in step 2), the first metal layer 300 and the second metal layer 600 are copper metal layers, and the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 are SiC layers to manufacture a copper current collector. Relevant performance tests were carried out on the copper current collector, and the test results are shown in Table 1.

[0082] Example 5 The manufacturing method and structure of the current collector in this embodiment are basically the same as those in Example 1, but the difference is in the composition of the fiber base layer 100. Specifically, the manufacturing steps of the current collector are as follows.

[0083] 1) Manufacturing the fiber base layer 100 Polyimide fiber and glass fiber were mixed and melted in a mass ratio of 98:2, and then extrusion-molded into a composite fiber. 120 parts of composite fiber, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica were uniformly mixed, and then uniformly laid in a net shape, followed by hot rolling and drying to produce a fiber base layer 100 with a thickness of 6 μm.

[0084] 2) Manufacturing of current collectors By using vacuum deposition technology, the first adhesive layer 200 and the second adhesive layer 500 with a thickness of 40 nm were respectively deposited on the upper and lower surfaces of the fiber-based layer 100 produced in step 1). However, the first adhesive layer 200 and the second adhesive layer 500 are nickel metal layers. Then, the first metal layer 300 and the second metal layer 600 with a thickness of 1000 nm were subsequently deposited on the first adhesive layer 200 and the second adhesive layer 500. However, the first metal layer 300 and the second metal layer 600 are aluminum metal layers. Then, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 with a thickness of 40 nm were subsequently deposited on the first metal layer 300 and the second metal layer 600. However, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 are nickel metal layers, that is, an aluminum current collector was obtained. The relevant performance test was carried out thereon, and the test results are shown in Table 1.

[0085] Example 6 The manufacturing method and structure of the current collector in this embodiment are basically the same as those in the embodiment 5, except that the first metal layer 300 and the second metal layer 600 in step 2) are copper metal layers to manufacture a copper current collector. The relevant performance tests were carried out, and the test results are shown in Table 1.

[0086] Example 7 The manufacturing method and structure of the current collector in this embodiment are basically the same as those in Example 1, but the difference is in the composition of the fiber base layer 100. Specifically, the manufacturing steps of the current collector are as follows.

[0087] 1) Manufacturing the fiber base layer 100 Polyacrylonitrile fiber and silica nanofiber were mixed and melted in a mass ratio of 85:15, and then extrusion-formed composite fiber. 50 parts of composite fiber, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica were uniformly mixed, and then uniformly laid in a net shape, followed by hot rolling and drying to produce a fiber base layer 100 with a thickness of 6 μm.

[0088] 2) Manufacturing of current collectors By using vacuum deposition technology, the first adhesive layer 200 and the second adhesive layer 500 with a thickness of 50 nm were respectively deposited on the upper and lower surfaces of the fiber-based layer 100 produced in step 1). However, the first adhesive layer 200 and the second adhesive layer 500 are nickel metal layers. Then, the first metal layer 300 and the second metal layer 600 with a thickness of 1000 nm were subsequently deposited on the first adhesive layer 200 and the second adhesive layer 500. However, the first metal layer 300 and the second metal layer 600 are aluminum metal layers. Then, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 with a thickness of 50 nm were subsequently deposited on the first metal layer 300 and the second metal layer 600. However, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 are nickel metal layers, that is, an aluminum current collector was obtained. The relevant performance test was carried out thereon, and the test results are shown in Table 1.

[0089] Example 8 The manufacturing method and structure of the current collector in this example are basically the same as those in Example 7, but the difference is that the materials of the first adhesive layer 200 and the second adhesive layer 500 are different. Specifically, the manufacturing steps of the current collector are as follows.

[0090] 1) Manufacturing the fiber base layer 100 Polyacrylonitrile fiber and silica nanofiber were mixed and melted in a mass ratio of 85:15, and then extrusion-formed composite fiber. 50 parts of composite fiber, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica were uniformly mixed, and then uniformly laid in a net shape, followed by hot rolling and drying to produce a fiber base layer 100 with a thickness of 6 μm.

[0091] 2) Manufacturing of current collectors By using vacuum deposition technology, the first adhesive layer 200 and the second adhesive layer 500 with a thickness of 50 nm were respectively deposited on the upper and lower surfaces of the fiber-based layer 100 produced in step 1). However, the first adhesive layer 200 and the second adhesive layer 500 are SiO2 layers. Then, the first metal layer 300 and the second metal layer 600 with a thickness of 1000 nm were subsequently deposited on the first adhesive layer 200 and the second adhesive layer 500. However, the first metal layer 300 and the second metal layer 600 are aluminum metal layers. Then, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 with a thickness of 50 nm were subsequently deposited on the first metal layer 300 and the second metal layer 600. However, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 are nickel metal layers, that is, an aluminum current collector was obtained. The relevant performance test was carried out thereon, and the test results are shown in Table 1.

[0092] Example 9 The manufacturing method and structure of the current collector in this example are basically the same as those in Example 6, but the difference is that the materials of the first adhesive layer 200 and the second adhesive layer 500 are different. Specifically, the manufacturing steps of the current collector are as follows.

[0093] 1) Manufacturing the fiber base layer 100 Polyimide fiber and glass fiber were mixed and melted in a mass ratio of 98:2, and then extrusion-molded into a composite fiber. 120 parts of composite fiber, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica were uniformly mixed, and then uniformly laid in a net shape, followed by hot rolling and drying to produce a fiber base layer 100 with a thickness of 6 μm.

[0094] 2) Manufacturing of current collectors By using vacuum deposition technology, the first adhesive layer 200 and the second adhesive layer 500 with a thickness of 40 nm were respectively deposited on the upper and lower surfaces of the fiber-based layer 100 produced in step 1). However, the first adhesive layer 200 and the second adhesive layer 500 are SiO2 layers. Then, the first metal layer 300 and the second metal layer 600 with a thickness of 1000 nm were subsequently deposited on the first adhesive layer 200 and the second adhesive layer 500. However, the first metal layer 300 and the second metal layer 600 are copper metal layers. Then, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 with a thickness of 40 nm were subsequently deposited on the first metal layer 300 and the second metal layer 600. However, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 are nickel metal layers, that is, a copper current collector was obtained. The relevant performance test was carried out thereon, and the test results are shown in Table 1.

[0095] Example 10 The manufacturing method and structure of the current collector in this comparative example are basically the same as those in Example 1, but the difference is that the materials of the first adhesive layer 200 and the second adhesive layer 500 are different. Specifically, the manufacturing steps of the current collector are as follows.

[0096] 1) Manufacturing the fiber base layer 100 Nylon 6 and titanium dioxide nanofibers were mixed and melted in a mass ratio of 98:2, and then extruded to form a composite fiber. 50 parts of the composite fiber, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica were mixed uniformly, and then laid uniformly in a net shape, followed by hot rolling and drying to produce a fiber base layer 100 with a thickness of 6 μm.

[0097] 2) Manufacturing of current collectors By using vacuum deposition technology, the first adhesive layer 200 and the second adhesive layer 500 with a thickness of 50 nm were respectively deposited on the upper and lower surfaces of the fiber-based layer 100 produced in step 1). However, the first adhesive layer 200 and the second adhesive layer 500 are Fe2O3 layers. Then, the first metal layer 300 and the second metal layer 600 with a thickness of 1000 nm were subsequently deposited on the first adhesive layer 200 and the second adhesive layer 500. However, the first metal layer 300 and the second metal layer 600 are aluminum metal layers. Then, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 with a thickness of 50 nm were subsequently deposited on the first metal layer 300 and the second metal layer 600. However, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 are nickel metal layers, that is, an aluminum current collector was obtained. The relevant performance test was carried out thereon, and the test results are shown in Table 1.

[0098] Example 11 The manufacturing method and structure of the current collector in this comparative example are basically the same as those in Example 1, but the differences are that the material of the inorganic fibers is different and the materials of the first adhesive layer 200 and the second adhesive layer 500 are different. Specifically, the manufacturing steps of the current collector are as follows.

[0099] 1) Manufacturing the fiber base layer 100 Nylon 6 and graphene fibers were mixed and melted in a mass ratio of 98:2, and then extrusion-formed composite fibers. 50 parts of composite fibers, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica were uniformly mixed, and then uniformly laid in a net shape, followed by hot rolling and drying to produce a fiber-based layer 100 with a thickness of 6 μm.

[0100] 2) Manufacturing of current collectors By using vacuum deposition technology, the first adhesive layer 200 and the second adhesive layer 500 with a thickness of 50 nm were respectively deposited on the upper and lower surfaces of the fiber-based layer 100 produced in step 1), where the first adhesive layer 200 and the second adhesive layer 500 are iron metal layers. Then, the first metal layer 300 and the second metal layer 600 with a thickness of 1000 nm were subsequently deposited on the first adhesive layer 200 and the second adhesive layer 500, where the first metal layer 300 and the second metal layer 600 are aluminum metal layers. Then, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 with a thickness of 50 nm were subsequently deposited on the first metal layer 300 and the second metal layer 600, where the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 are nickel metal layers, that is, an aluminum current collector was obtained. The relevant performance test was carried out thereon, and the test results are shown in Table 1.

[0101] Example 12 The manufacturing method and structure of the current collector in this comparative example are basically the same as those in Example 11, but the difference is that in step 2), the first metal layer 300 and the second metal layer 600 are copper metal layers, and a copper current collector is manufactured. Specifically, the manufacturing steps of the current collector are as follows.

[0102] 1) Manufacturing the fiber base layer 100 Nylon 6 and graphene fibers were mixed and melted in a mass ratio of 98:2, and then extrusion-formed composite fibers. 50 parts of composite fibers, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica were uniformly mixed, and then uniformly laid in a net shape, followed by hot rolling and drying to produce a fiber-based layer 100 with a thickness of 6 μm.

[0103] 2) Manufacturing of current collectors By using vacuum deposition technology, the first adhesive layer 200 and the second adhesive layer 500 with a thickness of 50 nm were respectively deposited on the upper and lower surfaces of the fiber-based layer 100 produced in step 1), where the first adhesive layer 200 and the second adhesive layer 500 are iron metal layers. Then, the first metal layer 300 and the second metal layer 600 with a thickness of 1000 nm were subsequently deposited on the first adhesive layer 200 and the second adhesive layer 500, where the first metal layer 300 and the second metal layer 600 are copper metal layers. Then, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 with a thickness of 50 nm were subsequently deposited on the first metal layer 300 and the second metal layer 600, where the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 are nickel metal layers, that is, a copper current collector was obtained. The relevant performance test was carried out thereon, and the test results are shown in Table 1.

[0104] Example 13 The manufacturing method and structure of the current collector of this comparative example are basically the same as those of Example 11, but the difference is that the material of the inorganic fibers is different. Specifically, the manufacturing steps of the current collector are as follows.

[0105] 1) Manufacturing the fiber base layer 100 Nylon 6 and carbon fiber were mixed and melted in a mass ratio of 98:2, and then extruded to form a composite fiber. 50 parts of the composite fiber, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica were mixed uniformly, and then laid uniformly in a net shape, followed by hot rolling and drying to produce a fiber base layer 100 having a thickness of 6 μm.

[0106] 2) Manufacturing of current collectors By using vacuum deposition technology, the first adhesive layer 200 and the second adhesive layer 500 with a thickness of 50 nm were respectively deposited on the upper and lower surfaces of the fiber-based layer 100 produced in step 1), where the first adhesive layer 200 and the second adhesive layer 500 are iron metal layers. Then, the first metal layer 300 and the second metal layer 600 with a thickness of 1000 nm were subsequently deposited on the first adhesive layer 200 and the second adhesive layer 500, where the first metal layer 300 and the second metal layer 600 are aluminum metal layers. Then, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 with a thickness of 50 nm were subsequently deposited on the first metal layer 300 and the second metal layer 600, where the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 are nickel metal layers, that is, an aluminum current collector was obtained. The relevant performance test was carried out thereon, and the test results are shown in Table 1.

[0107] Example 14 The manufacturing method and structure of the current collector of this comparative example are basically the same as those of Example 12, but the difference is that the material of the inorganic fibers is different. Specifically, the manufacturing steps of the current collector are as follows.

[0108] 1) Manufacturing the fiber base layer 100 Nylon 6 and carbon fiber were mixed and melted in a mass ratio of 98:2, and then extruded to form a composite fiber. 50 parts of the composite fiber, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica were mixed uniformly, and then laid uniformly in a net shape, followed by hot rolling and drying to produce a fiber base layer 100 having a thickness of 6 μm.

[0109] 2) Manufacturing of current collectors By using vacuum deposition technology, the first adhesive layer 200 and the second adhesive layer 500 with a thickness of 50 nm were respectively deposited on the upper and lower surfaces of the fiber-based layer 100 produced in step 1), where the first adhesive layer 200 and the second adhesive layer 500 are iron metal layers. Then, the first metal layer 300 and the second metal layer 600 with a thickness of 1000 nm were subsequently deposited on the first adhesive layer 200 and the second adhesive layer 500, where the first metal layer 300 and the second metal layer 600 are copper metal layers. Then, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 with a thickness of 50 nm were subsequently deposited on the first metal layer 300 and the second metal layer 600, where the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 are nickel metal layers, that is, a copper current collector was obtained. The relevant performance test was carried out thereon, and the test results are shown in Table 1.

[0110] Comparative Example 1 The manufacturing method and structure of the current collector in this comparative example are basically the same as those in Example 1, but the difference is that the fiber used in the fiber base layer 100 is only nylon 6. The specific steps are as follows.

[0111] 1) Manufacturing the fiber base layer 100 50 parts of nylon 6, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax and 0.2 parts of nano-silica were taken and mixed uniformly, and then uniformly laid out in a net-like shape, followed by hot rolling and drying to produce a fiber-based layer 100 having a thickness of 6 μm.

[0112] 2) Manufacturing of current collectors By using vacuum deposition technology, the first adhesive layer 200 and the second adhesive layer 500 with a thickness of 50 nm were respectively deposited on the upper and lower surfaces of the fiber-based layer 100 produced in step 1). However, the first adhesive layer 200 and the second adhesive layer 500 are nickel metal layers. Then, the first metal layer 300 and the second metal layer 600 with a thickness of 1000 nm were subsequently deposited on the first adhesive layer 200 and the second adhesive layer 500. However, the first metal layer 300 and the second metal layer 600 are aluminum metal layers. Then, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 with a thickness of 50 nm were subsequently deposited on the first metal layer 300 and the second metal layer 600. However, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 are nickel metal layers, that is, an aluminum current collector was obtained. The relevant performance test was carried out thereon, and the test results are shown in Table 1.

[0113] Comparative Example 2 This comparative example has a manufacturing method and structure of a current collector that are basically the same as those in Comparative Example 1, but differs in that the first metal layer 300 and the second metal layer 600 in step 2) are copper metal layers. The specific steps are as follows:

[0114] 1) Manufacturing the fiber base layer 100 50 parts of nylon 6, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax and 0.2 parts of nano-silica were taken and mixed uniformly, and then uniformly laid out in a net-like shape, followed by hot rolling and drying to produce a fiber-based layer 100 having a thickness of 6 μm.

[0115] 2) Manufacturing of current collectors By using vacuum deposition technology, the first adhesive layer 200 and the second adhesive layer 500 with a thickness of 50 nm were respectively deposited on the upper and lower surfaces of the fiber-based layer 100 produced in step 1). However, the first adhesive layer 200 and the second adhesive layer 500 are nickel metal layers. Then, the first metal layer 300 and the second metal layer 600 with a thickness of 1000 nm were subsequently deposited on the first adhesive layer 200 and the second adhesive layer 500. However, the first metal layer 300 and the second metal layer 600 are copper metal layers. Then, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 with a thickness of 50 nm were subsequently deposited on the first metal layer 300 and the second metal layer 600. However, the first oxidation-resistant layer 400 and the second oxidation-resistant layer 700 are nickel metal layers, that is, an aluminum current collector was obtained. The relevant performance test was carried out thereon, and the test results are shown in Table 1.

[0116] Comparative Example 3 The current collector of this comparative example has a manufacturing method and structure basically similar to those of Example 1, but differs in that the mass ratio of nylon 6 to titanium dioxide nanofibers in the composite fiber is 60:40.

[0117] Comparative Example 4 The current collector of this comparative example has a manufacturing method and a structure similar to those of the current collector of Example 1, but differs in that the first adhesive layer and the second adhesive layer are not provided.

[0118] The tensile elongation test method is as follows: one end of the fiber-based layer is clamped by the upper clamping head of the tensile tester, and the other end is clamped by the lower clamping head of the tensile tester, and held on the same axis. The parameters of the tester, such as specifications, speed, and unit, are set, and the stretched length and load value of the sample are measured and recorded during the test. The tensile elongation of the fiber-based layer is calculated based on the test results. The pressure density when measuring the tensile elongation is 4g / cm3 to 4.1g / cm3. Wherein, the pressure density refers to the ratio of the tensile force applied to the sample to the cross-sectional area of ​​the sample. The test conditions are specifically, the temperature is 20℃ to 25℃, and the relative humidity is 40% to 70%.

[0119] The peel strength test method is as follows. An 11 cm long tape is attached to a steel plate, and a 10 cm long current collector is attached to the tape. A 22 cm long tape is attached to the current collector, and the steel plate is fixed to a peel strength tester. The 22 cm long tape is bent into a U-shape, and the free end of the 22 cm long tape is clamped by the chuck of the peel strength tester. The peel strength tester is started, and the tape is pulled to separate the metal layer from the base layer, and the peel strength is measured. The test conditions are a temperature of 20°C to 25°C and a relative humidity of 40% to 70%.

[0120] The electrolyte wetting contact angle test method is as follows. The electrolyte is dropped vertically onto the surface of the current collector, and the contact angle between the droplet and the material surface is measured using a contact angle measuring device. The temperature is 20°C to 25°C, and the relative humidity is 40% to 70%. The electrolyte is ethylene carbonate.

[0121] The resistivity test method is as follows. The length and cross-sectional area of ​​the current collector sample are recorded, the current collector sample is placed on a measuring jig, good contact between the jig and the surface of the sample is ensured, and a certain amount of current is applied by a resistivity meter. The voltage across the sample is measured using a voltmeter. The resistivity of the sample is calculated from the resistivity formula using the measured current and voltage values. The specific measurement conditions are a temperature of 20°C to 25°C, a relative humidity of 40% to 70%, and a resistor pitch of the resistivity meter of 0.8mm to 1.2mm.

[0122] [Table 1]

[0123] The technical features of the above embodiments can be combined in any manner. For the sake of simplicity, all possible combinations of the technical features in the above embodiments are not described, but as long as there is no contradiction in the combination of these technical features, they should all be considered within the scope of the present specification.

[0124] It should be understood that the above examples are merely illustrative of some embodiments of the present invention, and the description is specific and detailed, but does not limit the scope of the present invention. It should be noted that a person skilled in the art can make some modifications and improvements without departing from the concept of the present invention, and all of these are within the scope of protection of the present invention. Therefore, the scope of protection of the present invention is subject to the scope of the appended claims.

[0125] (Additional Note) (Appendix 1) 1. A current collector comprising a fiber-based layer, A first adhesive layer and a second adhesive layer are provided on both surfaces of the fiber base layer, and the first adhesive layer and the second adhesive layer are provided with a first metal layer and a second metal layer on the surfaces away from the fiber base layer, respectively; The material composition of the fiber-based layer includes, by weight, 50-120 parts of composite fiber, 4.1-19 parts of inorganic filler, and an auxiliary, where the composite fiber includes organic fiber and inorganic fiber; A current collector characterized by:

[0126] (Appendix 2) The mass ratio of the organic fibers to the inorganic fibers is (70 to 99.9):(0.1 to 30). 2. The current collector according to claim 1,

[0127] (Appendix 3) The mass ratio of the organic fibers to the inorganic fibers is (90 to 99.9):(0.1 to 10). 3. The current collector according to claim 2,

[0128] (Appendix 4) the inorganic filler comprises one or more of calcium carbonate, borax and nanosilica; and / or and / or the organic fibers include one or more of polyethylene terephthalate fibers, polybutylene terephthalate fibers, polyethylene naphthalate fibers, polypropyl urethane fibers, polyurethane fibers, polycaprolactone fibers, nylon 6, nylon 66, polyimide fibers, polyacrylonitrile fibers, polyethylene oxide fibers, polyvinyl alcohol fibers, polyvinyl chloride fibers, polyvinylpyrrolidone fibers, cellulose acetate, ethylcyanoethylcellulose, polyaniline fibers, and polybenzimidazole fibers; and / or The inorganic fibers include one or more of graphene fibers, carbon fibers, glass fibers, ceramic fibers, metal oxide nanofibers, and silica nanofibers; 4. The current collector according to claim 1, wherein the current collector is a metal oxide.

[0129] (Appendix 5) The auxiliary includes one or more of a dispersant, a thickener, an emulsifier, and a binder; The dispersing agent comprises one or more of polyacrylamide, polyvinyl alcohol, sodium citrate, and sodium silicate; The viscosity increasing agent may comprise one or more of sodium hydroxypropyl methylcellulose, sodium hydroxyethyl methylcellulose, sodium carboxymethylcellulose, sodium methylcellulose and sodium alginate; The emulsifier comprises one or more of glyceryl monostearate, polyoxyethylene ether, and sodium dodecyl sulfate; The binder comprises sodium carboxymethyl cellulose and / or polyvinyl alcohol. 4. The current collector according to claim 1, wherein the current collector is a metal oxide.

[0130] (Appendix 6) The amount of the auxiliary agent added to the fiber base layer is 8.1 to 28 parts by weight, In the auxiliary, the dispersant is 2.5 to 9 parts by weight, the thickener is 3 to 8 parts by weight, the emulsifier is 0.1 to 2 parts by weight, and the binder is 2.5 to 9 parts by weight. 6. The current collector according to claim 5,

[0131] (Appendix 7) further comprising a first oxidation-resistant layer and a second oxidation-resistant layer; the first oxidation-resistant layer is located on a surface of the first metal layer remote from the first adhesive layer, the second oxidation-resistant layer is located on a surface of the second metal layer remote from the second adhesive layer, and the materials of the first oxidation-resistant layer and the second oxidation-resistant layer are each independently Al, Fe, Ni, Zn, Gr, Fe2O3, Al2O3, SiC, or Si3N4; 4. The current collector according to claim 1, wherein the current collector is a metal oxide.

[0132] (Appendix 8) the material of the first adhesive layer and the second adhesive layer are each independently Ni, Zn, Fe, Gr, SiO2, Al2O3, Fe2O3, or Si3N4; and / or The material of the first metal layer and the second metal layer is Al or Cu; 4. The current collector according to claim 1, wherein the current collector is a metal oxide.

[0133] (Appendix 9) the thickness of the fiber-based layer is between 2 μm and 8 μm; and / or the first adhesive layer and the second adhesive layer each have a thickness of 10 nm to 200 nm; and / or the first metal layer and the second metal layer each have a thickness of 100 nm to 2000 nm; and / or The first oxidation-resistant layer and the second oxidation-resistant layer each have a thickness of 10 nm to 100 nm. 9. The current collector according to claim 8,

[0134] (Appendix 10) At least one material of the first adhesive layer and the second adhesive layer is Fe, and the inorganic fibers include one or two of graphene fibers and carbon fibers; 4. The current collector according to claim 1, wherein the current collector is a metal oxide.

[0135] (Appendix 11) The inorganic fibers are selected from metal oxide nanofibers; The materials of the first adhesive layer and the second adhesive layer are each independently selected from a metal or a metal oxide; The current collector according to any one of claims 1 to 3.

[0136] (Appendix 12) The inorganic fibers are one or more selected from graphene fibers, carbon fibers, glass fibers, ceramic fibers, and silica nanofibers, and materials of the first adhesive layer and the second adhesive layer are each independently selected from non-metal oxides and non-metal nitrides; The current collector according to any one of claims 1 to 3.

[0137] (Appendix 13) A method for producing a current collector according to any one of claims 1 to 12, comprising the steps of: mixing the composite fiber, the inorganic filler and the auxiliary, and then rolling the resulting mixture to produce the fiber base layer; forming the first adhesive layer and the second adhesive layer on both sides of the fiber-based layer, respectively; and forming the first metal layer and the second metal layer on one side of the first adhesive layer and the second adhesive layer, respectively, facing away from the fiber-based layer; The present invention relates to a method for producing a current collector.

[0138] (Appendix 14) The current collector according to any one of claims 1 to 13 and an electrode active material layer located on a surface of the current collector. An electrode piece characterized by:

[0139] (Appendix 15) Including the electrode piece according to claim 14, 1. A battery comprising:

[0140] (Appendix 16) A plurality of electrode bodies according to claim 15, A battery pack characterized by:

[0141] (Appendix 17) 15. A battery pack comprising the cell of claim 15 or the battery pack of claim 16. 1. A power consuming device comprising:

Claims

1. 1. A current collector comprising a fiber-based layer, A first adhesive layer and a second adhesive layer are provided on both surfaces of the fiber base layer, and the first adhesive layer and the second adhesive layer are provided with a first metal layer and a second metal layer on the surfaces away from the fiber base layer, respectively; The material composition of the fiber-based layer includes, by weight, 50-120 parts of composite fiber, 4.1-19 parts of inorganic filler, and auxiliary, wherein the composite fiber includes organic fiber and inorganic fiber; A current collector characterized by:

2. The mass ratio of the organic fibers to the inorganic fibers is (70 to 99.9):(0.1 to 30); The current collector according to claim 1 .

3. The mass ratio of the organic fibers to the inorganic fibers is (90 to 99.9):(0.1 to 10); The current collector according to claim 2 .

4. said inorganic fillers include one or more of calcium carbonate, borax and nanosilica; and / or and / or the organic fibers include one or more of polyethylene terephthalate fibers, polybutylene terephthalate fibers, polyethylene naphthalate fibers, polypropyl urethane fibers, polyurethane fibers, polycaprolactone fibers, nylon 6, nylon 66, polyimide fibers, polyacrylonitrile fibers, polyethylene oxide fibers, polyvinyl alcohol fibers, polyvinyl chloride fibers, polyvinylpyrrolidone fibers, cellulose acetate, ethylcyanoethylcellulose, polyaniline fibers, and polybenzimidazole fibers. The inorganic fibers include one or more of graphene fibers, carbon fibers, glass fibers, ceramic fibers, metal oxide nanofibers, and silica nanofibers; The current collector according to any one of claims 1 to 3.

5. The auxiliary includes one or more of a dispersant, a thickener, an emulsifier, and a binder; the dispersing agent comprises one or more of polyacrylamide, polyvinyl alcohol, sodium citrate and sodium silicate; the viscosity increasing agent comprises one or more of sodium hydroxypropyl methylcellulose, sodium hydroxyethyl methylcellulose, sodium carboxymethylcellulose, sodium methylcellulose and sodium alginate; The emulsifier comprises one or more of glyceryl monostearate, polyoxyethylene ether, and sodium dodecyl sulfate; The binder comprises sodium carboxymethyl cellulose and / or polyvinyl alcohol. The current collector according to any one of claims 1 to 3.

6. The amount of the auxiliary agent added to the fiber base layer is 8.1 to 28 parts by weight, In the auxiliary, the dispersant is 2.5 to 9 parts by weight, the thickener is 3 to 8 parts by weight, the emulsifier is 0.1 to 2 parts by weight, and the binder is 2.5 to 9 parts by weight. The current collector according to claim 5 .

7. further comprising a first oxidation-resistant layer and a second oxidation-resistant layer; the first oxidation-resistant layer is located on a surface of the first metal layer remote from the first adhesive layer, the second oxidation-resistant layer is located on a surface of the second metal layer remote from the second adhesive layer, and materials of the first oxidation-resistant layer and the second oxidation-resistant layer are each independently Al, Fe, Ni, Zn, Gr, Fe2O3, Al2O3, SiC, or Si3N4; The current collector according to any one of claims 1 to 3.

8. the material of the first adhesive layer and the second adhesive layer is each independently Ni, Zn, Fe, Gr, SiO2, Al2O3, Fe2O3, or Si3N4; and / or The material of the first metal layer and the second metal layer is Al or Cu. The current collector according to any one of claims 1 to 3.

9. the thickness of said fibre-based layer is between 2 μm and 8 μm; and / or the first adhesive layer and the second adhesive layer each have a thickness of from 10 nm to 200 nm; and / or the first metal layer and the second metal layer each have a thickness of between 100 nm and 2000 nm; and / or The first oxidation-resistant layer and the second oxidation-resistant layer each have a thickness of 10 nm to 100 nm. The current collector according to claim 8 .

10. At least one material of the first adhesive layer and the second adhesive layer is Fe, and the inorganic fibers include one or two of graphene fibers and carbon fibers; The current collector according to any one of claims 1 to 3.

11. The inorganic fibers are selected from metal oxide nanofibers; The materials of the first adhesive layer and the second adhesive layer are each independently selected from a metal or a metal oxide; The current collector according to any one of claims 1 to 3.

12. The inorganic fibers are one or more selected from graphene fibers, carbon fibers, glass fibers, ceramic fibers, and silica nanofibers, and materials of the first adhesive layer and the second adhesive layer are each independently selected from non-metal oxides and non-metal nitrides; The current collector according to any one of claims 1 to 3.

13. A method for producing a current collector according to any one of claims 1 to 12, comprising the steps of: mixing the composite fiber, the inorganic filler and the auxiliary, and then rolling the resulting mixture to produce the fiber base layer; forming the first adhesive layer and the second adhesive layer on both sides of the fiber-based layer, respectively; and forming the first metal layer and the second metal layer on one side of the first adhesive layer and the second adhesive layer, respectively, facing away from the fiber-based layer; The present invention relates to a method for producing a current collector.

14. A current collector according to any one of claims 1 to 13, and an electrode active material layer located on a surface of the current collector. An electrode piece characterized by:

15. The electrode strip according to claim 14, 1. A battery comprising:

16. The electrode body according to claim 15, A battery pack characterized by:

17. A battery pack comprising the battery according to claim 15 or the battery pack according to claim 16.

1. A power consuming device comprising:

Citation Information

Patent Citations

  • Paper-based composite structure and battery

    CN108281666A